Penerapan Model Pembelajaran Blended Learning Dalam Meningkatkan Kemandirian dan Hasil Belajar Korespondensi - Rina Suryani Harahap (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to analyze the effectiveness of using learning tools based on the Blended Learning learning model by utilizing online learning applications in increasing student independence and learning outcomes in Correspondence subjects for class X SMK Negeri 1 Kisaran. This research was conducted at SMK Negeri 1 Kisaran, with a population of 72 people. The sample in this study was taken by purposive sampling technique. From the results of the data analysis of the control class, the learning independence score was 3.78 with the "Good" category while the experimental class was 4.40 with the "Very Good" category. The data on student learning outcomes can be seen from the posttest scores in the control class on average 77.92 with a standard deviation of 10,174 while in the experimental class the average learning outcome in the control class is 87.25 with a standard deviation of 9,802. The first hypothesis test is obtained by Fcount > Ftable (55.936 > 4.11) then Ha is accepted, while in the second hypothesis test Fcount > Ftable (216.906 > 4.11), then Ha is accepted. It can be concluded that the average independence and learning outcomes of experimental class students who are taught using the blended learning model with the help of online learning applications are higher than the control class taught using the conventional learning model.Â Keywords: blended learning; learning outcomes; learning independenceÂ Â Abstrak: Penelitian ini bertujuan untuk melakukan analisis terhadap efektivitas penggunakan perangkat pembelajaran berbasis model pembelajaran Blended Learning dengan memanfaatkan aplikasi pembelajaran online dalam meningkatkan kemandirian dan hasil belajar siswa pada mata pelajaran Korespondensi kelas X SMK Negeri 1 Kisaran. Penelitian ini dilaksanakan di SMK Negeri 1 Kisaran, dengan jumlah populasi 72 orang. Sampel dalam penelitian ini diambil dengan teknik purposive sampling. Dari hasil analisis data kelas kontrol skor kemandirian belajar sebesar 3,78 dengan kategori â€œBaikâ€ sedangkan kelas eksperimen sebesar 4,40 dengan kategori â€œSangat Baikâ€. Data hasil belajar siswa dilihat dari skor postest pada kelas kontrol rata-rata sebesar 77,92 dengan standar deviasi 10,174 sedangkan pada kelas eksperimen rata-rata hasil belajar sebesar 87,25 dengan standar deviasi 9,802. Uji hipotesis pertama diperoleh Fhitung > FÂÂtabel (55,936 > 4.11) maka Ha diterima, sedangkan pada uji hipotesis kedua FÂÂhitung > dariÂ  Ftabel (216,906 > 4.11), maka Ha diterima. Dapat disimpulkan bahwa rata-rata kemandirian dan hasil belajar siswa kelas eksperimen yang diajarkan dengan model pembelajaran blended learning dengan bantuan aplikasi pembelajaran online lebih tinggi dibandingkan dengan kelas kontrol yang diajarkan dengan model pembelajaran konvensional.Â Kata kunci: blended learning; hasil belajar; kemandirian belajar